Egressos da UFT/Unidade Cimba/Araguaína/TO membros da Comunidade de Remanescentes de Quilombolas Pé do Morro: análise dos impactos da educação superior à luz das perspectivas de desenvolvimento e liberdade de Amartya Sen e Paulo Freire - AZEVEDO, Raquel Torquato Rodrigues de (Universidade Federal do Tocantins, 2025)
This dissertation has the general objective of analyzing the possible effects of higher education to reduce social vulnerabilities and reach the liberating development of the members of the Quilombo Pé do Morro Remnant Community who acquired a higher education level via UFT / Cimba Unit / Araguaína-TO (2010-2019). From this objective, the specific objectives that aim to describe in general lines the historical process of people of African descent in Brazilian society arise, focusing on the struggle for integration; to verify if education, especially at the higher level, can be seen as an instrument of development and freedom in the light of the theories of Sen (2010) and Freire (1967, 1994, 1997), who defend development and education for freedom; to analyze how the collaborators / participants of the research, graduates of UFT who are members of CRQPM, understand the impacts of education, especially higher education, on their lives. It is a qualitative and descriptive-explanatory research; procedurally, it develops in stages that include bibliographic research, documentary and field research with data collection via questionnaire, concluding the course with analyzes of the information obtained in the various previous stages, in the light of the scientific theories that make up the theoretical framework (SEN, FREIRE), also supported by studies by other authors such as Spivak and Ribeiro. As for the analysis and results, we found that the creation of a social opportunity to access higher education is not capable of generating the expected effects if it is not associated with complementary material resources; fundamental levels of education impact on student performance at the higher level; higher education institutions must prepare to receive vulnerable people, according to their specificities (psychological support and permanence in the facilities); the educational level and the income level influence each other and in both directions; higher education has a positive impact on personal life and human development and contributes to the (re) elaboration of social and individual identity, the expansion of social visibility and the establishment and / or expansion of the place of speech; higher education serves as an instrument of individual and social liberation through knowledge and the critical capacity it develops, enabling the expansion of options and well-informed decision-making. By way of final considerations, we can say that education is an important factor in reducing social vulnerability, because, among other points, it contributes to the processes of social and individual identification, linking to professionalization, social visibility and the place of speech. It provides the development of the capacity to carry out social and political analyzes and criticisms, based on the resources that people acquire from it, in the sense of Freire's thought (1967). It opens paths to development as a freedom defended by Sen (2010), by raising the levels of knowledge and expanding the capacity and competence to make choices, make decisions, effectively take advantage of social opportunities and exercise freedoms more fully. However, for there to be effective development as freedom and real social integration, it is necessary to have public policies that expand access and social opportunities.